Analisis pengaruh Financial Literacy dan Locus of Control sebagai variabel moderating terhadap Management Behaviour - Emawati Natan; Linda Mahastanti (Owner : Riset dan Jurnal Akuntansi, 2022)
Financial management Behavior needs to be carried out by every individual, including students. However, not all individuals are accustomed to financial management behavior. Financial management behavior in students is thought to be influenced by financial literacy, student locus of control through locus of control as a moderating variable. The purpose of this study was to analyze the effect of financial literacy and locus of control on financial management behavior with locus of control as a moderating variable. Quantitative research is the  type of research used. Questionnaires were used as a data collection technique. The total population of the study was 2,338 active undergraduate students. Purposive sampling was used for sampling. Classical assumption test, validity test, reliability test and regression analysis were used as a technique for data analysis and used SPSS 21 software. This study resulted in 1) There is a positive and significant effect of financial literacy on financial management behavior in students. 2) There is a positive and significant influence of locus of control on financial management behavior in students. 3) There is an influence of financial literacy on financial management behavior with locus of control as a moderating variable.